2017
DOI: 10.1073/pnas.1616464114
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio dynamics and photoionization mass spectrometry reveal ion–molecule pathways from ionized acetylene clusters to benzene cation

Abstract: The growth mechanism of hydrocarbons in ionizing environments, such as the interstellar medium (ISM), and some combustion conditions remains incompletely understood. Ab initio molecular dynamics (AIMD) simulations and molecular beam vacuum-UV (VUV) photoionization mass spectrometry experiments were performed to understand the ion-molecule growth mechanism of small acetylene clusters (up to hexamers). A dramatic dependence of product distribution on the ionization conditions is demonstrated experimentally and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 56 publications
3
35
0
Order By: Relevance
“…To elucidate ion-molecule growth dynamics in hydrocarbons, we chose mixed acetylene-ethylene clusters 53 and pure acetylene clusters. 54 The experimental set up essentially has two controls -one can tune the photon energy to precisely ionize a moiety and secondly, change the ionization distance to probe various regions of an expansion as demonstrated earlier with methanol. This work focused mainly on the formation of (C2H2)(C2H2), (C2H2)(C2H4), and (C2H4)(C2H4) dimers.…”
Section: Ion and Neutral Growth Pathways In Methanol Clusters And Inmentioning
confidence: 99%
See 2 more Smart Citations
“…To elucidate ion-molecule growth dynamics in hydrocarbons, we chose mixed acetylene-ethylene clusters 53 and pure acetylene clusters. 54 The experimental set up essentially has two controls -one can tune the photon energy to precisely ionize a moiety and secondly, change the ionization distance to probe various regions of an expansion as demonstrated earlier with methanol. This work focused mainly on the formation of (C2H2)(C2H2), (C2H2)(C2H4), and (C2H4)(C2H4) dimers.…”
Section: Ion and Neutral Growth Pathways In Methanol Clusters And Inmentioning
confidence: 99%
“…Guided by these earlier results, we now focus on the decomposition mechanisms of larger acetylene clusters leading to ring formation. 54 This is illustrated in figure 6, where ion-molecule reactions with in-source ionization can lead to fragmentation products. Notice the absence of m/z 52 and 78, which are acetylene dimer and trimer respectively.…”
Section: From Van Der Waals To Covalent Bonding In Ionized Acetylene mentioning
confidence: 99%
See 1 more Smart Citation
“…43,44 Mass spectrometry has been applied to characterize the products resulting from photoionization of acetylene clusters, and peaks with mass corresponding to intact clusters with the formula (C2H2)n + (where n is an integer), were observed. 45 In a recent study, we used ab initio molecular dynamics (AIMD) to model the results of those experiments. 45 Our results showed that chemically bonded molecules can be formed subsequent to ionization of neutral van der Waals clusters.…”
Section: Introductionmentioning
confidence: 99%
“…45 In a recent study, we used ab initio molecular dynamics (AIMD) to model the results of those experiments. 45 Our results showed that chemically bonded molecules can be formed subsequent to ionization of neutral van der Waals clusters. Upon ionization, the clusters are able to spontaneously rearrange, and undergo geometric relaxation.…”
Section: Introductionmentioning
confidence: 99%